Biomimetic architectured Kevlar/polyimide composites with ultra-light, superior anti-compressive and flame-retardant properties. (1st February 2022) - Zheng, Liangang; Zhang, Kun; Liu, Li; Xu, Fujun
Abstract: Lightweight, high strength, and flame-retardant properties are highly required for practical applications of composites, such as in areas of aerospace, aircraft, and automobiles. However, it is challenging to achieve the above properties simultaneously due to the intrinsic conflict between lightweight and excellent mechanical performance. Herein, we overcome this conflict in a 3D Kevlar/polyimide composite (K/PIC) innovatively by mimicking the structural features of the beetle's elytra. As a result, the K/PIC has a void content of 84% and a low volume density of 0.23 g/cm 3, but it can support more than 16 000 times its own weight without any damage. It exhibits a specific strength of 23.5 MPa/g·cm −3, which is superior to that of many other reported lightweight composites. Additionally, the as-prepared K/PIC could not be ignited and could retain around 93.2% of its original compressive strength even after being subjected to the flame of an alcohol burner for 300 s. The results demonstrate that similar lightweight, high strength, and flame-retardant composites can be fabricated by this underlying principle in future and be applied in extreme environments, such as aeronautics and aerospace. Graphical abstract: Image 1 Highlights: A novel bio-inspired 3D Kevlar/Polyimide composite (3DKPIC) is proposed Its ultralow density (0.197 g/cm 3 ) is essential for the aerospace applications It can withstand the pressure of 16 000 times its own weight without being damaged 3DKPIC cannot be ignited and has 92.3% residual compressive strength after test